The Clinical Impact of Cardiology Consultation Prior to Major Vascular Surgery. Issue 1 (January 2018) - Davis, Frank M.; Park, Yeo June; Grey, Scott F.; Boniakowski, Anna E.; Mansour, M. Ashraf; Jain, Krishna M.; Nypaver, Timothy; Grossman, Michael; Gurm, Hitinder; Henke, Peter K.
Abstract : Objective: To understand statewide variation in preoperative cardiology consultation prior to major vascular surgery and to determine whether consultation was associated with differences in perioperative myocardial infarction (poMI). Summary Background Data: Medical consultation prior to major vascular surgery is obtained to reduce perioperative risk. Despite perceived benefit of preoperative consultation, evidence is lacking specifically for major vascular surgery on the effect of preoperative cardiac consultation. Methods: Patient and clinical data were obtained from a statewide vascular surgery registry between January 2012 and December 2014. Patients were risk stratified by revised cardiac risk index category and compared poMI between patients who did or did not receive a preoperative cardiology consultation. We then used logistic regression analysis to compare the rate of poMI across hospitals grouped into quartiles by rate of preoperative cardiology consultation. Results: Our study population comprised 5191 patients undergoing open peripheral arterial bypass (n = 3037), open abdominal aortic aneurysm repair (n = 332), or endovascular aneurysm repair (n = 1822) at 29 hospitals. At the patient level, after risk-stratification by revised cardiac risk index category, there was no association between cardiac consultation and poMI. At the hospital level, preoperative cardiac consultation varied substantially between hospitals (6.9%–87.5%, P <0.001). High preoperative consulting hospitals (rate >66%) had a reduction in poMI (OR, 0.52; confidence interval: 0.28–0.98; P <0.05) compared with all other hospitals. These hospitals also had a statistically greater consultation rate with a variety of medical specialties. Conclusions: Preoperative cardiology consultation for vascular surgery varies greatly between institutions, and does not appear to impact poMI at the patient level. However, reduction of poMI was noted at the hospitals with the highest rate of preoperative cardiology consultation as well as a variety of medical services, suggesting that other hospital culture effects play a role. Abstract : Supplemental Digital Content is available in the text